I miracoli - gli straordinari segni di Dio: Un discernimento filosofico - teologico dei miracoli - Relja, Hrvoje (Alpha Omega, 2013)
Theological analysis shows that miracles are signs of extraordinary Divine Providence which testify and reveal God’s salvific action in the world and which, as can be argued philosophically, are intrinsically rational because they are performed in accordance with the Eternal law (Lex aeterna) which transcends the lawfulness and rationality of the created world. Statements of the Magisterium of the Church which point to the rationality of miracles and their role in the history of salvation entail a theologically certain conclusion (theologice certa) that miracles can be recognized as such through rational argumentation. A philosophical-theological analysis of miracles shows that human responsibility in forming an attitude towards a miracle is of a different kind than the responsibility towards revelation, the credibility of which the aforementioned miracle signifies. The acceptance of miracles on the basis of their distinctive rationality, can be scientifically certain while their acceptance on the basis of revelation, which is always effected by faith, involves only a moral certainty.